Histoire des croisades - Michaud, Joseph François, 1767-1839. (Paris)
6 c. (1. c. 675 s., [3] katlı sayfa harita ; 2. c. 654 s., [2] katlı sayfa harita ; 3. c. 659 s., [2] katlı sayfa harita ; 4. c. 595 s. ; 5. c. 688 s. ; 6. c. 548 s.)